The CYP19A1 (TTTA)n Repeat Polymorphism May Affect the Prostate Cancer Risk: Evidence from a Meta-Analysis. Issue 3 (May 2021) - Guo, Lei; Liu, Yanan; Liu, Lijun; Shao, Shixiu; Cao, Yanwei; Guo, Jiaming; Niu, Haitao
Abnormal aromatase (CYP19A1) expression may participate in prostate cancer (PCa) carcinogenesis. However, the results of studies on the CYP19A1 gene polymorphisms and PCa are conflicting. This meta-analysis aimed to systematically evaluate the associations between the CYP19A1 Arg264Cys polymorphism and the (TTTA)n repeat polymorphism and PCa. Electronic databases (PubMed, EmBase, ScienceDirect, and Cochrane Library) were comprehensively searched to identify eligible studies. The strength of the association between the Arg264Cys polymorphism and PCa was assessed by pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) in allelic, dominant, recessive, homozygous, and heterozygous genetic models. To analyze the impact of the (TTTA)n repeat polymorphism, we sequentially took the N-repeat allele (where N equals 7, 8, 10, 11, 12, and 13) as the minor allele and the sum of all the other alleles as the major allele. The ORs and 95% CIs were calculated in the allelic model; this analysis was performed individually for each repeat number. Pooled estimates of nine studies addressing the Arg264Cys polymorphism indicated that this polymorphism was not associated with PCa risk in the overall population or in the Caucasian or Asian subgroups. The 8-repeat allele in the (TTTA)n repeat polymorphism increased PCa risk in the overall population (OR = 1.34, 95% CI = 1.14–1.58, p = .001) and in the subgroup with population-based (PB) controls (OR = 1.41, 95% CI = 1.13–1.74, p = .002) as well as in the subgroup using capillary electrophoresis to identify this polymorphism (OR = 1.34, 95% CI = 1.09–1.65, p = .006).The meta-analysis indicated that the CYP19A1 (TTTA)n repeat polymorphism, but not the Arg264Cys polymorphism, may affect PCa risk.